2005
DOI: 10.1002/jmv.20312
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intra‐person cytomegalovirus infection in Malawian families

Abstract: Sequence polymorphisms in the gN and gO genes of cytomegalovirus (CMV) amplified from mouth rinse and urine samples of 19 Malawian patients with Kaposi's sarcoma (KS) and 58 of their first-degree relatives were investigated. CMV-DNA was amplified from 41 people (53%) from either the gN or gO region in at least one sample, from 14 people (18%) in both domains in at least one sample, and from 13 (17%) in either domain in both samples. Twenty-one (51%) were seropositive for human immunodeficiency virus-1 (HIV). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Peripartum CMV transmission rates were similar between breastfed and formula-fed infants, and overall transmission rates were similar in both our intent-to-treat and as-treated analyses, suggesting that the high rate of CMV transmission in the formula-feeding arm was not due to misclassification of feeding modality, but rather to the acquisition of CMV via non-breast milk modes of transmission. Infections can originate from other contacts from both within and outside the household [27], and because we did not sequence CMV in this study, we are unable to definitively link transmissions between mothers and infants.…”
Section: Discussionmentioning
confidence: 92%
“…Peripartum CMV transmission rates were similar between breastfed and formula-fed infants, and overall transmission rates were similar in both our intent-to-treat and as-treated analyses, suggesting that the high rate of CMV transmission in the formula-feeding arm was not due to misclassification of feeding modality, but rather to the acquisition of CMV via non-breast milk modes of transmission. Infections can originate from other contacts from both within and outside the household [27], and because we did not sequence CMV in this study, we are unable to definitively link transmissions between mothers and infants.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, early reports of diverse HCMV infections also demonstrated that HCMV sampled from different organs of healthy individuals could differ in gB genotype composition [14,41]. This finding has been supported in subsequent work studying other genomic loci [10,33,42]. Quantitative descriptions of the diversity have demonstrated significant differences in the level of diversity between compartments, with blood populations appearing more diverse than urine or intraocular populations [7,22].…”
Section: Tissue Compartmentalization Of Hcmv In Human Hostsmentioning
confidence: 83%
“…Indeed, early reports of diverse HCMV infections also demonstrated that HCMV sampled from different organs of healthy individuals could differ in gB genotype composition [14,41]. This finding has been supported in subsequent work studying other genomic loci [10,33,42]. Quantitative descriptions of the diversity have demonstrated significant differences in the level of diversity between compartments, with blood populations appearing more diverse than urine or intraocular populations [7,22].…”
Section: Tissue Compartmentalization Of Hcmv In Human Hostsmentioning
confidence: 84%